Serena Williams and (the perception of) violence: intersectionality, the performance of blackness, and women's professional tennis. Issue 9 (14th July 2020) - Tredway, Kristi
ABSTRACT: Serena Williams is the most accomplished tennis player in the open era of professional tennis. She is also a Black woman which figures prominently in how she is (mis)understood in tennis. Using intersectionality as an interpretive framework, we aim to show how Serena fits within the social structure of tennis which was created within the white, upper-class social milieu. Within the lineage from this historic milieu, Serena is sometimes perceived to be violent; however, that perception highlights the ways in which Serena is positioned differently in this setting than her counterparts. Her outbursts are not more egregious than those of other players; however, Serena's performance of blackness disrupts the expected tennis imaginary and attaches to her the extra imaginings of those features attached to blackness such as urban mannerisms, lack of respect for authority, and violence, which unjustly add extra weight for Serena to bear.